PERAN ASISTEN SUTRADARA DALAM PRODUKSI FILM DOKUMENTER URANG KANEKES: A CULTURE ADAPTING TECHNOLOGY - Ibrahim Lee (2023)
The purpose of writing this final project is to find out the role of the Assistant Director in the Production of the Documentary Film Urang Kanekes: A Culture Adapting Technology, in which this film tells the story of the Outer Baduy Tribe who live full of local wisdom and slowly begin to adapt to the introduction of modernization into their lives. That is the reason for the author to make this final project, apart from the author's curiosity about the role of an assistant director in producing a documentary film. The final result of making the Documentary Film Urang Kanekes: A Culture Adapting Technology shows that the Outer Baduy Tribe actually takes advantage of the influx of modernization in the form of technology and digital media to help their daily lives such as selling online, promoting the Baduy Tribe itself and their crafts through social media, being invited to exhibitions in Jakarta as a result of people seeing their art or handicrafts being uploaded to social media such as Instagram and Youtube. The author also gains experience and knowledge about how to become an assistant director, with the responsibilities and burdens that must be borne for the success of the production of this documentary so that it becomes a useful lesson and knowledge for the author in the future when he will pursue work in the film field, especially if the author want to become an assistant director.